To combine the two terms \(-5\sqrt{7}\) and \(-4\sqrt{7}\), you can add their coefficients since they are like terms.
\[ -5\sqrt{7} - 4\sqrt{7} = (-5 - 4)\sqrt{7} = -9\sqrt{7} \]
Therefore, the answer in simplest form is:
\[ \boxed{-9\sqrt{7}} \]
–5√7–4√7
1 answer
To combine the two terms \(-5\sqrt{7}\) and \(-4\sqrt{7}\), you can add their coefficients since they are like terms.
\[ -5\sqrt{7} - 4\sqrt{7} = (-5 - 4)\sqrt{7} = -9\sqrt{7} \]
Therefore, the answer in simplest form is:
\[ \boxed{-9\sqrt{7}} \]